The Journey to Destination ‘the Netherlands’ : A Study on the changing Representation of the Netherlands - Wesseling, Dorien (2020)
The purpose of this study was to research and get a better understanding about the choices behind the representation of a destination on a tourism website by a destination marketing organisation (DMO). The study wants to get more insights on the motivations behind the created image of a destination when looking at the fields of tourism, marketing and intercultural communication. The research questions are: ‘What motives do the national Dutch Destination Management Organisation have for the representation of the Netherlands on their new website?’ and ‘How has the representation of the Netherlands changed from the old to the new website of the national Dutch Destination Management Organisation?’. The research consists of two types of qualitative research: semi-structured interviews and an analyses of the old and new version of the DMO’s tourism website. The interviews have been analysed by using the method of thematic qualitative analysis and the analysis of the websites by using the method of semiotics and a model of visual rhetorical interpretation. The translation of the brand, the ideal target group and strategies to portray the Netherlands are all in development to create their ideal representation of the Netherlands. The brand also describes the country as: open, inclusive and innovative. The switch from both websites shows there is a big change in the content, especially the visual content. The changes that have been made, together with the reasons and motives that have been given by the participants, show that the image of Holland has changed or is changing to a diverse, contemporary and less cliché new Netherlands.